1978
DOI: 10.1002/mpo.2950040302
|View full text |Cite
|
Sign up to set email alerts
|

Nonsystemic treatment of metastatic tumors of the liver—a review

Abstract: Hepatic metastasis is usually quite resistant to conventional systemic chemotherapy. Nonsystemic treatment of metastatic tumors of the liver include surgical resection; infusion of chemotherapeutic agent(s), either via hepatic artery or portal vein; ligation of hepatic artery; radiotherapy; and other more investigative approaches (isolation perfusion, cryosurgery, liver transplantation, etc). The relative applicability, results, and limitations of each of these therapeutic modalities are reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1979
1979
1990
1990

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Mori et al [22] reported a selective destruction of the tumor without damage to the normal liver after ligation of the hepatic artery for metastatic gastric carcinoma. The response to surgical ligation is temporary, in part due to the formation of collateral circulation that may occur almost instantaneously [23].…”
Section: Hepatic Artery Embolization (Hae)mentioning
confidence: 99%
“…Mori et al [22] reported a selective destruction of the tumor without damage to the normal liver after ligation of the hepatic artery for metastatic gastric carcinoma. The response to surgical ligation is temporary, in part due to the formation of collateral circulation that may occur almost instantaneously [23].…”
Section: Hepatic Artery Embolization (Hae)mentioning
confidence: 99%